Effectiveness of Sengon Ethyl Acetate Extract and Bamboo Liquid Smoke as Disinfectants - Anisa, Divia; Marlina, Rina; Juniar, Fadia Rahma; Nurjaman, Deni; Fadhila, Feldha; Mayuri, Nindya Sekar; Rumidatul, Alfi (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2025)
The absence of environmental sanitation can influence the transmission of infectious diseases, exemplified as toilets tainted with dangerous microbes. Prevention typically employs disinfectants; nevertheless, their adverse effects might lead to skin and respiratory discomfort. Flavonoids, tannins, and saponins in sengon wood possess antibacterial properties and can serve as alternative materials. The study aimed to assess the efficacy of combining sengon wood extract and bamboo stem liquid smoke as a disinfectant. The experimental methodology employed in vitro testing through an inhibitory assay and in vivo testing utilizing a swab on the surface, assessing the effects pre- and post-swabbing. The in vitro results indicated that the most substantial inhibitory zone was observed with a 40:60 ratio for Salmonella typhimurium ATCC 25241, measuring 11.8 mm; for Candida albicans ATCC 10231, a 30:70 ratio yielded 5.33 mm; and for Aspergillus flavus ATCC 9643, a 30:70 ratio resulted in 5.5 mm. In vivo, swabs from the table yielded an average reduction of 92% in bacterial colonies and 73% in fungal colonies. Conclusion: The amalgamation of sengon twig wood extract and bamboo stem liquid smoke exhibits potential as a disinfectant. Keywords: Liquid smoke, bamboo sticks, disinfectant, sengon wood